Health complaints among adolescents: Associations with more screen-based behaviours and less physical activity. (October 2015) - Marques, Adilson; Calmeiro, Luís; Loureiro, Nuno; Frasquilho, Diana; de Matos, Margarida Gaspar
Abstract: In this study, we investigated the relationship between screen-based behaviours, physical activity, and health complaints (headaches, feeling low, irritability, and nervousness). Screen-based behaviour included TV viewing, computer use, and time spent playing video games. Data were collected from 4462 Portuguese adolescents (2394 girls) aged 11–16 years. Girls who reported engaging in more screen-based behaviour (hours/day) also reported having more headaches, feeling lower, being more irritable, and feeling more nervous. Boys who reported more screen time were more irritable. Physical activity (times/week) was negatively associated with reports of feeling nervous among girls, and with headaches, feeling low, irritability, and feeling nervous among boys. Considering that time spent using the computer is related with more health complaints, and physical activity was related with fewer health complaints among boys, it is important to develop strategies to reduce adolescents' computer screen time, and to promote physical activity.